Validation of smartphone addiction scale-short version among Malaysian undergraduate students - Wong, Boon Yew; Yeo, Kee Jiar; Lee, Shih-Hui; Handayani, Lina (Intelektual Pustaka Media Utama, 2023)
Smartphone addiction scale-short version or SAS-SV has been consistently found to have one-factor structure and proven as a valid and reliable instrument to measure smartphone addiction. However, it has not been validated among the undergraduate students in Malaysia. With the aim to address such empirical gap, this study has validated its one-factor structure and assessed its reliability and validity among the 680 undergraduate students in Universiti Teknologi Malaysia (UTM). Its content validity was first demonstrated. Subsequently, the findings of confirmatory factor analysis (CFA) have supported and confirmed its one-factor model. Furthermore, its convergent validity and reliability were also proven to be satisfactory. Taken together, this study has demonstrated that SAS-SV is an instrument that can reliably and accurately measure or identify smartphone addiction symptoms among the undergraduate students in Malaysia.